2022
DOI: 10.1039/d2nr01911f
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on the photocatalytic action of titanium dioxide on phenol elucidated using comprehensive multiphase NMR

Abstract: First application of CMP-NMR to heterogeneous catalysis, we discover a region where organics experience restricted diffusion and are preferentially degraded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…At the same time, the local dynamics that reduce the CP efficiency also narrow the 1 H linewidth allowing low power 1 H decoupling to become more efficient, and as such a signal appears in the “solution‐state”. Ultimately, it is clear that SASSY can be used to distinguish the degree of rigidity and may appeal to those investigating biological tissue (tissue stiffness, hard scaffolds), [19] or solid–liquid interactions such as substrate–catalyst binding/fouling, [20, 21] protein immobilization at interfaces [22, 23] and other processes involving changes in multiple phases such as swelling or drying.…”
Section: Figurementioning
confidence: 99%
“…At the same time, the local dynamics that reduce the CP efficiency also narrow the 1 H linewidth allowing low power 1 H decoupling to become more efficient, and as such a signal appears in the “solution‐state”. Ultimately, it is clear that SASSY can be used to distinguish the degree of rigidity and may appeal to those investigating biological tissue (tissue stiffness, hard scaffolds), [19] or solid–liquid interactions such as substrate–catalyst binding/fouling, [20, 21] protein immobilization at interfaces [22, 23] and other processes involving changes in multiple phases such as swelling or drying.…”
Section: Figurementioning
confidence: 99%
“…Our group recently published a report monitoring photocatalysis using Comprehensive MultiPhase Nuclear Magnetic Resonance (CMP-NMR). 11 CMP-NMR creates a series of NMR spectra of individual phases defined by their diffusion (solutions, gels) and dipolar interactions (solids). These include the solution phase (bulk solution molecules far from colloidal surface), the solid phase (molecules tightly bound or adsorbed to the colloidal surface), and a restricted diffusion phase (molecules at the interface between the previous phases which are interacting with the colloid but not tightly bound).…”
mentioning
confidence: 99%
“…12−14 A detailed description of the origin and interpretation of these spectra in photocatalytic systems has been provided in previous studies. 11 This previous work identified that molecules in a diffusion restricted phase, which were distinct from those bound to the colloidal surface, were preferentially targeted by reactive oxygen species (ROS) generated at the catalyst surface.…”
mentioning
confidence: 99%
See 2 more Smart Citations